PENGGUNAAN Terminalia catappa UNTUK PENGOBATAN INFEKSI BAKTERI Aeromonas hydrophila PADA IKAN BETOK (Anabas testudineus) - Maryani, Maryani; Bungas, Kartika; Mahfudz, Mahfudz (Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, 2024)
Aeromonas hydrophila bacterial attack is one of the factors that affect aquaculture activities and cause losses. One alternative that can be done to treat diseases caused by bacteria is to utilize antibacterials that are environmentally friendly and harmless to the ecosystem, one of which is by utilizing ketapang leaves (Terminalia catappa). Ketapang leaves contain antibacterial compounds such as flavonoids, alkaloids, tannins, triterpenoids/steroids, saponins. This study aims to determine the dose of ketapang leaves to treat diseases caused by Aeromonas hydrophila bacteria in betok fish seeds (Anabas testudineus) with various treatments. The method used in this study was a completely randomized design with four treatments (A, B, C, D) and three replicates (1, 2, 3) namely A (control), B (1000 ppm), C (2000 ppm), and D (3000 ppm) using betok fish as test fish infected with the pathogen Aeromonas hydrophila, then given treatment in the form of soaking using ketapang leaf extract. The results showed that treatment due to disease with Aeromonas hydrophila bacteria in betok fish using ketapang leaf extract was very effective in treatments B, C and D. The best dose was found in treatment D with a dose of 3000 ppm, followed by treatment C with a dose of 2000 ppm and treatment B with a dose of 1000 ppm. The highest growth rate of betok fish fry was found in treatment D at 7.66%, followed by treatment C at 6.33%, and treatment B at 5.33%.